2017
DOI: 10.1007/s13187-017-1300-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Knowledge, Attitudes, and Practices among Dentists in Khartoum State, Sudan

Abstract: The incidence of oral cancer is rising in the Sudan. Detecting oral cancer at an early stage is the most effective means of improving survival and reducing morbidity from disease. Aim:The aim of the present study was to determine the knowledge, attitude and practice of dentists related to oral cancer prevention and early detection in public dental clinics in Khartoum State, Sudan. Materials and Methods:A cross-sectional survey using an administered structured questionnaire was carried out. The questionnaire co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
4
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 82 publications
6
27
4
5
Order By: Relevance
“…In addition, it was observed that 88.5% to 100% of participants referred patients with suspected malignant lesion to a specialist. The results of our study are different from Ahmad and Naidoo study in which only 52.2% of referrals were reported (Ahmed and Naidoo, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, it was observed that 88.5% to 100% of participants referred patients with suspected malignant lesion to a specialist. The results of our study are different from Ahmad and Naidoo study in which only 52.2% of referrals were reported (Ahmed and Naidoo, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Twenty-four studies were conducted in America [17,18,22,39,43,[50][51][52][55][56][57][58][59][60][61][62][63]65,67,71,73,77,78,81], 20 in Europe [12,27,38,42,[44][45][46][47][48][49]53,54,64,66,[68][69][70]72,79,80] [21,25], two in Australia [26,31], and one in Japan and Australia [28] (Tables 3 and 4). The reporting of literature review on the KAP key question showed 55 studies using SPIDER and 11 usi...…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our indings, Ahmed and Naidoo reported that most of the participants referred their patient to an oral medicine specialist, while remaining of the participants was attributed to oral and maxillofacial surgeon, general surgeon and dentists. This inding could indicate the presence of confusion among general dentists of the referral system of these diseases (Ahmed and Naidoo, 2019). Joanne.et.al., 46% of the dental practitioners considered that their knowledge regarding Oral cancer was insuf icient (Clovis et al, 2002).…”
Section: Resultsmentioning
confidence: 98%